Reaction path study of conformational transitions and helix formation in a tetrapeptide. - Czerminski, R (1989)
Conformational transitions between the 112 stable states of the tetrapeptide isobutyryl-Ala3-NH-methyl (IAN) are studied theoretically. The objective of the investigation is to advance the understanding of helix formation and of conformational transitions in polypeptides. The possible reaction paths between extended chain and helical configurations are examined in detail. The study of the multiple reaction paths in this 48-atom molecule became possible due to development of a new computational algorithm. It is shown that the helix-coil transitions in IAN follow a sequence of local dihedral flips and that the number of the available routes for the transition is significantly lower than in a random search. A quasi-melting point is obtained at 5 +/- 1 kcal (1 cal = 4.18 J)/mol above the lowest energy minimum. Below this point the molecule is trapped in one or very few minima, and above it the molecule hops between a large number of configurations.